Preparation method of high-temperature-resistant, high-strength, high-conductivity and high-heat-conduction copper-niobium heterogeneous nano-composite microfilaments
Through the extreme plastic deformation process of copper and niobium winding composite combined with bundled pulling, copper-niobium isomerized nanocomposite filaments with high strength, excellent high temperature thermal stability and radiation resistance are prepared, solving the problem that existing copper-based micro filaments are difficult to meet multiple performance requirements at the same time.
Patent Information
- Application Number
- CN202411768324.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Existing copper-based microfilaments are difficult to meet the needs of high temperature thermal stability, radiation resistance, high strength, high conductivity and high thermal conductivity at the same time, and are difficult to apply in extreme service environments.
The copper-niobium isomerial nanocomposite microfilaments with an alternating internal structure of copper and niobium winding composite combined with cluster drawing were prepared with an alternating distribution of copper and niobium isomeric nanocomposite microfilaments with a strong texture orientation of several nanometers to more than ten nanometers with an alternating distribution of copper, niobium strip core wire and low-energy copper-niobium amorphous interface.
The copper-niobium isomerized nanocomposite microfilaments have high tensile strength, good bending, tensile plasticity, excellent high-temperature thermal stability, radiation resistance and strong electrical matching, filling the performance gap that cannot be achieved in the existing technology.
Smart Images

Figure CN119608820A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature resistant, high-strength and high-conductivity composite copper wires, and specifically relates to a method for preparing high-temperature resistant, high-strength, high-conductivity and thermally conductive copper-niobium heterostructured nanocomposite micro-wires. Background Art
[0002] High-performance copper-based micro-wires are key basic materials for the development of high-tech fields such as nuclear power, optoelectronics, microelectronics, aviation, and aerospace. They are also an important support for the development of advanced equipment and information technology. They are mainly used as signal transmission lines for sensor systems in pressurized water reactors, semiconductor and integrated circuit bonding wires, high-end medical electron beam lines, intelligent robotic arm connection lines, aerospace signal transmission lines, and internal transmission lines of flexible electronic devices. They are required to have high-temperature thermal stability, radiation resistance, high strength, high conductivity, and high thermal conductivity. At present, the copper-based micro-wires on the domestic market are mainly copper wires, copper-silver wires, and copper-tin wires prepared by the melting-drawing process. However, it is difficult for the copper-based micro-wires prepared by the melting-drawing process to achieve a single crystal structure and obtain high conductivity; at the same time, both pure copper wires and copper alloy wires have poor thermal stability and poor high-temperature stress relaxation resistance, and they are difficult to use in nuclear radiation service environments. More importantly, the purification of the melt and the uniform distribution of alloy elements in the melting process are difficult to achieve and require a lot of manpower, material resources, and financial resources.
[0003] Relevant academic research and field applications show that the current copper-based micro-wire preparation process faces the problems of uneven composition and strong plastic and strong electrical matching. For pure copper micro-wires, their recrystallization temperature is relatively low (≤300°C), and they are difficult to use in high-temperature environments; in addition, based on the principle of work hardening, the strength of pure copper wires is improved by drawing deformation while sacrificing the excellent electrical conductivity of pure copper. For copper-silver and copper-tin micro-wires, the recrystallization temperatures of silver and tin are relatively lower, 150°C and -71°C, respectively. Although the addition of copper and tin elements provides electrical conductivity and thermal conductivity of copper-based micro-wires, their high-temperature thermal stability is further reduced. Therefore, the copper and copper-based micro-wires currently produced on the market are difficult to simultaneously meet the performance requirements of high-temperature thermal stability, radiation resistance, high strength, high electrical conductivity and high thermal conductivity, and are difficult to be applied in extremely responsible service environments, especially in the fields of nuclear power, aviation and aerospace.
[0004] Therefore, it is an important issue that needs to be solved urgently to design new copper-based composite material structures and components, propose new copper-based micro-wire processing and forming processes, and develop new high-performance copper-based micro-wires, so that the prepared copper-based micro-wires can have high-temperature thermal stability, radiation resistance, high strength, high conductivity and high thermal conductivity. It is of great significance to realize its application in extremely complex service environments such as nuclear reactors and aerospace, and to solve the problem of poor high-temperature service performance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing high-temperature resistant, high-strength, high-conductivity and high-thermal conductivity copper-niobium heterostructured nanocomposite microfilaments in view of the deficiencies of the above-mentioned prior art. The method adopts the extreme plastic deformation process of copper and niobium winding composite combined with bundle drawing to obtain copper-niobium heterostructured nanocomposite microfilaments with an internal structure of alternating distribution of single crystal-like strong texture orientation of several nanometers to more than ten nanometers of copper and niobium strip core wires and low-energy copper-niobium amorphous interfaces. The microfilaments have high tensile strength and good bending and stretching plasticity, excellent high-temperature thermal stability and high-temperature stress relaxation resistance, as well as excellent radiation resistance and excellent strong electrical matching, solving the problem that existing copper and copper alloy microfilaments cannot have high-temperature thermal stability, high strength, high conductivity, high thermal conductivity, radiation resistance and good bending plasticity.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilaments, characterized in that the method comprises the following steps:
[0007] Step 1: alternately arrange copper strips and niobium strips of the same thickness in layers and wind them into a cylinder, and then place them in an oxygen-free copper sheath to obtain a copper-niobium winding assembly composite sheath, vacuum degassing and vacuum welding the copper-niobium winding assembly composite sheath to make the interior of the oxygen-free copper sheath present a vacuum oxygen-free state, and then homogenize heating and isothermal hot extrusion deformation to form a weak connection between the internal copper layer and the niobium layer to obtain a copper-niobium composite extruded rod, and then perform multiple straight drawing, intermediate annealing and coil drawing on the copper-niobium composite extruded rod to obtain a copper-niobium composite wire with a hexagonal cross-section;
[0008] Step 2: The copper-niobium composite wire with a hexagonal cross-section obtained in step 1 is used as a core wire for bundle assembly and then placed in an oxygen-free copper sheath to obtain a multi-core structure copper-niobium bundle assembly composite sheath, and the multi-core structure copper-niobium bundle assembly composite sheath is vacuum degassed and vacuum welded to make the interior of the oxygen-free copper sheath present a vacuum oxygen-free state, and then homogenized heating and isothermal hot extrusion deformation are performed to form a weak connection between the inner core wire and the outer copper layer to obtain a copper-niobium multi-core composite extruded rod, and then the copper-niobium multi-core composite extruded rod is subjected to multiple straight drawing, intermediate annealing and coil drawing to obtain a copper-niobium multi-core composite round wire;
[0009] Step 3: After vacuum heat treatment, the copper-niobium multi-core composite round wire obtained in step 2 is subjected to a first multi-pass drawing and a first vacuum annealing treatment in sequence, and then a second multi-pass drawing and a second vacuum annealing treatment are sequentially performed, and then a third multi-pass drawing is sequentially performed, and after a final annealing heat treatment, a copper-niobium heterogeneous nanocomposite fine wire is obtained.
[0010] The present invention prepares a copper-niobium composite extruded rod by winding a copper strip and a niobium strip and then placing them in a sheath, and then subjecting them to homogeneous heating and isothermal hot extrusion deformation to obtain a copper-niobium composite extruded rod, and then drawing to obtain a copper-niobium composite wire with a hexagonal cross-section; then, the rods are bundled and assembled and placed in a sheath, and then subjecting them to homogeneous heating and isothermal hot extrusion deformation to obtain a copper-niobium multi-core composite extruded rod, and then drawing to obtain a copper-niobium multi-core composite round wire; and then, after multiple drawing passes, intermediate vacuum annealing treatment and final annealing heat treatment, a copper-niobium heterogeneous nano-composite fine wire is obtained.
[0011] First, since niobium has a high melting point (~2468°C) and a high recrystallization temperature (~1200°C) as well as high strength and good plasticity, and also has an elastic modulus similar to that of copper (the elastic modulus of copper is about 129GPa, and the elastic modulus of niobium is about 105GPa), the present invention obtains a copper and niobium strip-shaped core wire with a strong texture orientation similar to a single crystal and an alternating distribution of the internal structure, and a low-energy copper-niobium amorphous interface, through the extreme plastic deformation process of copper and niobium winding composite-bundle drawing, and induces considerable geometric required dislocations on both sides of the interface. This structure simultaneously induces nanoscale effects, gradient effects, and interface effects, and simultaneously acts on the copper-niobium heterogeneous nanocomposite microfilaments, while ensuring that the strength of the copper-niobium heterogeneous nanocomposite microfilaments is continuously improved, so that it maintains good plasticity and ensures its continuous and continuous deformation. Finally, the copper-niobium heterogeneous nanocomposite microfilaments prepared by the present invention have high tensile strength and good bending and tensile plasticity, solving the contradiction between strong and plastic matching of metals.
[0012] In addition, the high-temperature thermal stability of niobium and the excellent plasticity of copper composite nanowires improve the strong plasticity and high-temperature thermal stability of copper-niobium heterostructured nanocomposite microwires, especially the parallel and alternating distribution of copper and niobium strip core wire structure of several nanometers to more than ten nanometers, which makes the copper-niobium heterostructured nanocomposite microwires have excellent high-temperature thermal stability and high-temperature stress relaxation resistance; the geometrically required dislocation structure introduced by the low-energy copper-niobium amorphous interface and the gradient strain on both sides of the interface makes the movement and annihilation of dislocations in the copper-niobium heterostructured nanocomposite microwires slow under irradiation, thus making them resistant to radiation; and after extreme plastic deformation, the copper core wire structure of several nanometers to more than ten nanometers with strong texture orientation nearly similar to single crystal has very few grain boundaries inside, which makes it have higher electrical conductivity and achieves excellent strong electrical matching; the alternating distribution of copper core wires and niobium filaments makes the copper-niobium heterostructured nanocomposite microwires have thermal conductivity similar to that of copper. Under the above-mentioned combined effects, the copper-niobium heterostructured nanocomposite microfilaments of the present invention have the characteristics of high temperature resistance, high strength and plasticity, high electrical conductivity and high thermal conductivity, which solves the problem that the existing copper and copper alloy microfilaments cannot have high temperature thermal stability, high strength, high electrical conductivity, high thermal conductivity, radiation resistance and good bending plasticity.
[0013] The above-mentioned method for preparing a high-temperature resistant, high-strength, high-conductivity and thermally conductive copper-niobium heterostructured nanocomposite microfilament is characterized in that the thickness of the copper strip and the niobium strip in step 1 are both 0.1mm to 0.5mm, the diameter of the cylinder is Φ95mm to Φ115mm, the inner diameter of the oxygen-free copper sheath is 100mm to 120mm, and the wall thickness is 15mm to 30mm; the diameter of the copper-niobium composite extruded rod is Φ30mm to Φ50mm. The present invention effectively regulates the niobium element content by controlling the thickness of the winding copper strip and the niobium strip, the diameter of the cylinder, the inner diameter and the wall thickness of the oxygen-free copper sheath, and ensures that the copper strip and the niobium strip achieve excellent strength / plasticity and strength / electricity matching performance, thereby controlling the niobium content and the scale and distortion degree of the niobium core wire, regulating the internal dislocation type, density and movement behavior, stress / strain distribution and level, so that the prepared copper-niobium heterostructured nanocomposite microfilament has the best plastic deformation ability, and obtains the nearest strength, conductivity and high temperature temperature and radiation resistance matching.
[0014] The above-mentioned method for preparing a high-temperature resistant, high-strength, high-conductivity and high-thermal conductivity copper-niobium heterostructured nanocomposite microfilament is characterized in that the mass proportion of niobium element in the copper-niobium winding assembly composite sheath in step 1 is 20% to 25%, the temperature of the vacuum degassing is 300°C to 400°C, the time is 3h to 6h, the vacuum welding adopts vacuum electron beam sealing welding, and the vacuum degree is 1×10 -5 Pa~1×10 -4 Pa, the welding passes are 5 times; the temperature of the homogenizing heating is 680℃~720℃, the time is 2.5h~3.5h, the temperature of the isothermal hot extrusion deformation is 680℃~720℃, and the extrusion ratio is 7~9.
[0015] The above-mentioned method for preparing high-temperature resistant, high-strength, high-electrical and thermally conductive copper-niobium heterostructured nanocomposite microwires is characterized in that the deformation rate of the multiple straight drawing passes in step one is 15% to 17%, the intermediate annealing temperature is 670°C to 720°C, the time is 2h to 4h, and the deformation rate of the disk drawing pass is 12% to 15%; the opposite side distance of the hexagonal cross section is 4.5mm to 3.6mm.
[0016] Typically, in step 2 of the present invention, the number of cores of the hexagonal copper-niobium composite wires used as core wires for bundle assembly is 800 to 1200.
[0017] The present invention controls the size and number of the core wires for cluster assembly, regulates the copper / niobium interface density and the size of the copper and niobium core wires in the micro-wires, and further regulates the influence of scale effect and interface effect on the strength and plasticity of the copper-niobium heterostructured nano-composite micro-wires, thereby achieving continuous deformation of high-strength copper-niobium heterostructured nano-composite micro-wires with excellent bending plasticity after deformation.
[0018] The above-mentioned method for preparing high-temperature resistant, high-strength, high-electrical and thermally conductive copper-niobium heterostructured nanocomposite microfilaments is characterized in that the inner diameter of the oxygen-free copper sheath in step 2 is 100mm to 120mm, and the diameter of the copper-niobium multi-core composite extruded rod is Φ30mm to Φ50mm.
[0019] The above-mentioned method for preparing high-temperature resistant, high-strength, high-conductivity and high-thermal conductivity copper-niobium heterostructured nano-composite micro-wires is characterized in that the temperature of the vacuum degassing in step 2 is 300°C to 400°C, and the time is 3h to 6h; the temperature of the homogenous heating is 700°C to 720°C, and the time is 2.5h to 3.5h; the temperature of the isothermal hot extrusion deformation is 700°C to 720°C, and the extrusion ratio is 7 to 9.
[0020] The above-mentioned method for preparing a high-temperature resistant, high-strength, high-conductivity and high-thermal conductivity copper-niobium heterostructured nano-composite micro-wire is characterized in that the deformation rate of the multiple straight drawing passes in step 2 is 15% to 17%, the intermediate annealing temperature is 670°C to 720°C, the time is 2h to 4h, and the deformation rate of the coil drawing pass is 12% to 15%; the diameter of the copper-niobium multi-core composite round wire is Φ4mm to Φ12mm.
[0021] The above-mentioned method for preparing a high-temperature resistant, high-strength, high-conductivity and thermal conductivity copper-niobium heterostructured nano-composite micro-wire is characterized in that the temperature of the vacuum heat treatment in step three is 650°C to 700°C, and the time is 2.5h to 3.5h; the total deformation rate of the first multi-pass drawing is 85% to 90%, the pass deformation rate is 7% to 10%, and the temperature of the first vacuum annealing treatment is 650°C to 700°C, and the time is 1h; the total deformation rate of the second multi-pass drawing is 95% to 98%, the pass deformation rate is 6% to 8%, the temperature of the second vacuum annealing treatment is 550°C to 600°C, and the time is 1h; the total deformation rate of the third multi-pass drawing is 85% to 90%, the pass deformation rate is 12% to 24%, and the temperature of the final annealing heat treatment is 200°C to 400°C, and the time is 1h to 3h.
[0022] The above-mentioned method for preparing high-temperature resistant, high-strength, high-electrical and thermally conductive copper-niobium heterostructured nanocomposite microwires is characterized in that the wire diameter of the copper-niobium heterostructured nanocomposite microwires in step three is 0.05 mm to 0.15 mm.
[0023] The present invention controls the niobium content by controlling the sizes of copper strips, niobium strips, copper sheaths and the number of filaments used for bundled structures, thereby ensuring excellent high-strength plasticity and high-electricity matching; by controlling the size of each wire step, combined with controlling each step of annealing and drawing process, continuous deformation of the wire is achieved, thereby obtaining copper-niobium heterostructured nanocomposite microfilaments with excellent performance.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. The present invention adopts winding composite-degassing-welding-extrusion-drawing deformation, cluster composite-degassing-welding-extrusion-drawing deformation, annealing-drawing deformation-annealing-drawing deformation-annealing-drawing deformation-annealing process to obtain copper-niobium heterogeneous nanocomposite microfilaments with an internal structure of alternatingly distributed single crystal-like strong texture orientation of several nanometers to more than ten nanometers copper and niobium strip core wires and low-energy copper-niobium amorphous interface, so that the copper-niobium heterogeneous nanocomposite microfilaments have high tensile strength (tensile strength of 1000MPa to 1500MPa) and good bending and tensile plasticity (elongation at break of 2% to 5%), excellent high-temperature thermal stability and high-temperature stress relaxation resistance (softening temperature of 700°C or above), as well as excellent radiation resistance and excellent strong electrical matching (conductivity of 50% IACS or above).
[0026] 2. Compared with the copper wire, copper-silver wire and copper-tin wire prepared by the existing smelting-drawing process, the purification treatment of the melt and the control of the uniform distribution of alloy elements in the smelting process are difficult, and the uneven distribution of the precipitated phase, the internal defects introduced in the smelting and solidification process, and the uneven residual stress introduced in the wire deformation process easily cause the wire to break during the wire drawing process, thus making it difficult to prepare continuous kilometer-long copper-based micro-wires. The present invention adopts a niobium strip with good plasticity and a copper strip for winding and compounding, which can easily achieve continuous and uniform deformation of continuous copper-niobium heterogeneous micro-wires, and a disordered amorphous interface is formed at the copper-niobium interface after extreme plastic deformation, which greatly reduces local stress and effectively solves the problem of difficulty in deformation of the copper-niobium heterogeneous micro-wires due to the residual stress inside. At the same time, the preparation process of the present invention only involves extrusion, drawing and heat treatment, which is simpler and easier to control than smelting-drawing, and the preparation process is safe and easy to operate.
[0027] 3. The extreme plastic deformation process of the present invention is simple and easy to realize industrial mass production. At the same time, by stacking and winding the copper strip and the niobium strip to make a copper-niobium composite wire bundle assembly and then performing extreme plastic deformation, it is easy to achieve the uniformity of the internal structure of the copper-niobium composite micro-wire and obtain a core wire with a scale of more than ten nanometers to several nanometers, which solves the problems of organizational segregation, uneven reinforcement phase scale and uneven composition in the current preparation process of elastic copper-based micro-wires using smelting and powder metallurgy methods, and ensures the uniformity of the mechanical properties of the copper-niobium heterogeneous nano-composite micro-wires. In addition, the niobium core wire structure with a scale of more than ten nanometers to several nanometers and the low-energy copper-niobium amorphous interface with a scale of several nanometers inside the copper-niobium heterogeneous nano-composite micro-wires increase the recrystallization temperature of the micro-wires, so that they have a higher temperature thermal stability and achieve their high temperature resistance. The alternating distribution of copper and niobium inside the micro-wires ensures that the thermal conductivity of the copper-niobium heterogeneous nano-composite micro-wires is similar to that of pure copper, filling the gap in technical effects that cannot be achieved by the smelting-drawing process.
[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are some actual products with different diameters and corresponding measurement diagrams during the preparation of copper-niobium heterostructured nanocomposite microwires in Example 2 of the present invention.
[0030] Figure 2 This is a microstructure diagram of the copper-niobium heterogeneous nanocomposite microwires prepared in Example 2 of the present invention.
[0031] Figure 3 SEM images of the spheroidization of the internal niobium nanocore wires of the copper-niobium heterostructured nanocomposite microwires prepared in Example 2 of the present invention at room temperature 20°C and when heated to 700°C, 800°C and 900°C.
[0032] Figure 4 This is a tensile stress-strain curve of the copper-niobium heterostructured nanocomposite microwires prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] Example 1
[0034] This embodiment includes the following steps:
[0035] Step 1: Alternately arrange copper strips and niobium strips with a thickness of 0.5 mm in layers and wind them into a cylinder with a diameter of Φ95 mm, and then place them in an oxygen-free copper sheath with an inner diameter of 100 mm and a wall thickness of 30 mm to obtain a copper-niobium winding assembly composite sheath with a niobium element mass ratio of 25%. The copper-niobium winding assembly composite sheath is vacuum degassed at a temperature of 300°C for 3 hours, and vacuum electron beam sealing is performed with a vacuum degree of 1×10 -5 Pa~1×10 -4 Pa, 5 welding passes, so that the interior of the oxygen-free copper sheath is in a vacuum oxygen-free state, and then homogenization heating at a temperature of 680°C for 2.5 hours and isothermal hot extrusion deformation at a temperature of 680°C and an extrusion ratio of 7 are performed, so that the internal copper layer and the niobium layer form a weak connection, and a copper-niobium composite extruded rod with a diameter of Φ30 mm is obtained, and then the copper-niobium composite extruded rod is subjected to multi-pass straight drawing with a pass deformation rate of 15%, intermediate annealing at a temperature of 670°C for 2 hours, and coil drawing with a pass deformation rate of 12%, to obtain a copper-niobium composite wire with a hexagonal cross-section and a width across edges of 3.6 mm;
[0036] Step 2: 1200 copper-niobium composite wires with a hexagonal cross-section obtained in step 1 are used as core wires for bundle assembly and then placed in an oxygen-free copper sheath with an inner diameter of 100 mm to obtain a multi-core copper-niobium bundle assembly composite sheath, and the multi-core copper-niobium bundle assembly composite sheath is subjected to vacuum degassing at a temperature of 300° C. for 3 hours, and vacuum welding is performed to make the interior of the oxygen-free copper sheath present a vacuum oxygen-free state, and then homogenous heating at a temperature of 700° C. for 2.5 hours and isothermal hot extrusion deformation at a temperature of 700° C. and an extrusion ratio of 7 are performed to form a weak connection between the outer copper layer of the internal core wire, so as to obtain a copper-niobium multi-core composite extruded rod with a diameter of Φ30 mm, and then the copper-niobium multi-core composite extruded rod is subjected to multi-pass straight drawing with a pass deformation rate of 15%, intermediate annealing at a temperature of 670° C. for 2 hours, and coil drawing with a pass deformation rate of 12%, to obtain a copper-niobium multi-core composite round wire with a diameter of Φ4 mm;
[0037] Step 3, the copper-niobium multi-core composite round wire obtained in step 2 is subjected to vacuum heat treatment at a temperature of 650°C for 2.5 hours, and then the first multi-pass drawing with a total deformation rate of 85% and a pass deformation rate of 7% is carried out in sequence, and the first vacuum annealing treatment with a temperature of 650°C for 1 hour is carried out in sequence, followed by the second multi-pass drawing with a total deformation rate of 95% and a pass deformation rate of 6%, and the second vacuum annealing treatment with a temperature of 550°C for 1 hour, and then the third multi-pass drawing with a total deformation rate of 85% and a pass deformation rate of 12% is carried out in sequence, and after the final annealing heat treatment at a temperature of 200°C for 1 hour, a copper-niobium heterogeneous nano-composite micro-wire with a wire diameter of 0.05 mm is obtained.
[0038] Example 2
[0039] This embodiment includes the following steps:
[0040] Step 1: Alternately arrange copper strips and niobium strips with a thickness of 0.25 mm in layers and wind them into a cylinder with a diameter of Φ100 mm, and then place them in an oxygen-free copper sheath with an inner diameter of 110 mm and a wall thickness of 25 mm to obtain a copper-niobium winding assembly composite sheath with a niobium element mass ratio of 22.5%. The copper-niobium winding assembly composite sheath is vacuum degassed at a temperature of 350°C for 4.5 hours, and vacuum electron beam sealing is performed with a vacuum degree of 1×10 -5 Pa~1×10 -4Pa, 5 welding passes, so that the interior of the oxygen-free copper sheath is in a vacuum oxygen-free state, and then homogenization heating at a temperature of 700°C for 3.5 hours and isothermal hot extrusion deformation at a temperature of 700°C and an extrusion ratio of 8 are performed, so that the internal copper layer and the niobium layer form a weak connection, and a copper-niobium composite extruded rod with a diameter of Φ45 mm is obtained. The copper-niobium composite extruded rod is then subjected to multi-pass straight drawing with a pass deformation rate of 16%, intermediate annealing at a temperature of 700°C for 3 hours, and coil drawing with a pass deformation rate of 13.5%, to obtain a copper-niobium composite wire with a hexagonal cross-section and a side distance of 4 mm;
[0041] Step 2: 1000 copper-niobium composite wires with a hexagonal cross-section obtained in step 1 are used as core wires for bundle assembly and then placed in an oxygen-free copper sheath with an inner diameter of 110 mm to obtain a multi-core copper-niobium bundle assembly composite sheath, and the multi-core copper-niobium bundle assembly composite sheath is subjected to vacuum degassing at a temperature of 350° C. for 4.5 hours, and vacuum welding is performed to make the interior of the oxygen-free copper sheath present a vacuum oxygen-free state, and then homogenous heating at a temperature of 710° C. for 3 hours and isothermal hot extrusion deformation at a temperature of 710° C. and an extrusion ratio of 8 are performed to form a weak connection between the outer copper layer of the internal core wire, so as to obtain a copper-niobium multi-core composite extruded rod with a diameter of Φ40 mm, and then the copper-niobium multi-core composite extruded rod is subjected to multi-pass straight drawing with a pass deformation rate of 16%, intermediate annealing at a temperature of 700° C. for 3 hours, and coil drawing with a pass deformation rate of 13.5%, to obtain a copper-niobium multi-core composite round wire with a diameter of Φ5.5 mm;
[0042] Step 3: The copper-niobium multi-core composite round wire obtained in step 2 is subjected to vacuum heat treatment at a temperature of 680°C for 3 hours, and then the first multi-pass drawing with a total deformation rate of 87% and a pass deformation rate of 8%, the first vacuum annealing treatment at a temperature of 680°C for 1 hour are carried out in sequence, followed by the second multi-pass drawing with a total deformation rate of 96% and a pass deformation rate of 7%, the second vacuum annealing treatment at a temperature of 580°C for 1 hour, and then the third multi-pass drawing with a total deformation rate of 87% and a pass deformation rate of 18%. After the final annealing heat treatment at a temperature of 250°C for 1 hour, a copper-niobium heterogeneous nanocomposite fine wire with a wire diameter of 0.113 mm is obtained.
[0043] Figure 1 These are some actual products with different diameters and corresponding measurement diagrams during the preparation of copper-niobium heterostructured nanocomposite microwires in this embodiment.
[0044] Figure 2Figure 2 is a microstructure diagram of the copper-niobium heterostructured nanocomposite microwire prepared in this embodiment, wherein Figure (a) is a TEM bright field phase image of the copper-niobium heterostructured nanocomposite microwire, Figure (b) is a high-resolution image enlarged in the elliptical frame in Figure (a), Figure (c) is a distribution diagram of the niobium lamellar core wire in the copper-niobium heterostructured nanocomposite microwire, and Figure (d) is an energy spectrum diagram of the copper-niobium heterostructured nanocomposite microwire. It can be seen from Figures (a) to (d) that the size of the copper and niobium core wires in the copper-niobium heterostructured nanocomposite microwires is about ten nanometers, and the size of the copper-niobium interface is less than ten nanometers. A dragon ridge-like pattern appears at the copper-niobium interface in Figure (b), indicating that the interface absorbs considerable geometric dislocations inside the copper and niobium core wires, which greatly reduces the distortion and dislocation of the copper and niobium core wires and can maintain good thermal stability at high temperatures.
[0045] Figure 3 The SEM images of the spheroidization of the internal niobium nanocore wires of the copper-niobium heterostructured nanocomposite microwires prepared in this example at room temperature 20°C and at temperatures of 700°C, 800°C and 900°C. Figure 3 It can be seen that when the copper-niobium heterostructured nanocomposite microwires are heated to 700°C, the niobium nanowires begin to spheroidize, and the spheroidization phenomenon is not obvious; when the copper-niobium heterostructured nanocomposite microwires are heated to 800°C, the niobium nanowires begin to spheroidize obviously; when the copper-niobium heterostructured nanocomposite microwires are heated to 800°C, the niobium nanowires are completely spheroidized; it can be seen that the copper-niobium heterostructured nanocomposite microwires have good thermal temperature properties, and their anti-softening temperature is above 700°C.
[0046] Figure 4 The tensile stress-strain curve of the copper-niobium heterostructured nanocomposite microfilaments prepared in this example is shown in FIG. Figure 4 It can be seen that the tensile strength of the copper-niobium heterostructured nanocomposite microfilaments is greater than 1400 MPa, and the elongation at break is greater than 2.5%.
[0047] After testing, the thermal diffusion coefficient and thermal conductivity of the copper-niobium heterostructured nanocomposite microwires prepared in this embodiment are shown in Table 1 below.
[0048] Table 1
[0049]
[0050] It can be seen from Table 1 that at different service temperatures, the thermal conductivity of the copper-niobium heterogeneous nanocomposite microwires is approximately between 360W / (m·K) and 370W / (m·K), which is close to the thermal conductivity of pure copper 400W / (m·K). This indicates that the addition of the thermally stable phase niobium core wire has a relatively small weakening effect on the thermal conductivity of the copper-niobium nanocomposite micromaterial, and the copper-niobium nanocomposite micromaterial still has excellent thermal conductivity.
[0051] Example 3
[0052] This embodiment includes the following steps:
[0053] Step 1: Alternately arrange copper strips and niobium strips with a thickness of 0.1 mm in layers and wind them into a cylinder with a diameter of Φ115 mm, and then place them in an oxygen-free copper sheath with an inner diameter of 120 mm and a wall thickness of 15 mm to obtain a copper-niobium winding assembly composite sheath with a niobium element mass ratio of 20%. The copper-niobium winding assembly composite sheath is vacuum degassed at a temperature of 400°C for 6 hours, and vacuum electron beam sealing is performed with a vacuum degree of 1×10 -5 Pa~1×10 -4 Pa, 5 welding passes, so that the interior of the oxygen-free copper sheath is in a vacuum oxygen-free state, and then homogenous heating at a temperature of 720°C for 3.5 hours and isothermal hot extrusion deformation at a temperature of 720°C and an extrusion ratio of 9 are performed, so that the internal copper layer and the niobium layer form a weak connection, and a copper-niobium composite extruded rod with a diameter of Φ50 mm is obtained, and then the copper-niobium composite extruded rod is subjected to multi-pass straight drawing with a pass deformation rate of 17%, intermediate annealing at a temperature of 720°C for 4 hours, and coil drawing with a pass deformation rate of 15%, to obtain a copper-niobium composite wire with a hexagonal cross-section and a width across edges of 4.5 mm;
[0054] Step 2: 800 copper-niobium composite wires with a hexagonal cross-section obtained in step 1 are used as core wires for bundle assembly and then placed in an oxygen-free copper sheath with an inner diameter of 120 mm to obtain a multi-core copper-niobium bundle assembly composite sheath, and the multi-core copper-niobium bundle assembly composite sheath is subjected to vacuum degassing at a temperature of 400° C. for 6 hours, and vacuum welding is performed to make the interior of the oxygen-free copper sheath present a vacuum oxygen-free state, and then homogenous heating at a temperature of 720° C. for 3.5 hours and isothermal hot extrusion deformation at a temperature of 720° C. and an extrusion ratio of 9 are performed to form a weak connection between the outer copper layer of the internal core wire, so as to obtain a copper-niobium multi-core composite extruded rod with a diameter of Φ50 mm, and then the copper-niobium multi-core composite extruded rod is subjected to multi-pass straight drawing with a pass deformation rate of 17%, intermediate annealing at a temperature of 720° C. for 4 hours, and coil drawing with a pass deformation rate of 15%, to obtain a copper-niobium multi-core composite round wire with a diameter of Φ12 mm;
[0055] Step 3: The copper-niobium multi-core composite round wire obtained in step 2 is subjected to vacuum heat treatment at a temperature of 700°C for 3.5 hours, and then the first multi-pass drawing with a total deformation rate of 90% and a pass deformation rate of 10% is carried out in sequence, and the first vacuum annealing treatment with a temperature of 700°C and a time of 1 hour is carried out in sequence, followed by the second multi-pass drawing with a total deformation rate of 98% and a pass deformation rate of 8%, and the second vacuum annealing treatment with a temperature of 600°C and a time of 1 hour, and then the third multi-pass drawing with a total deformation rate of 90% and a pass deformation rate of 24% is carried out in sequence, and after the final annealing heat treatment at a temperature of 400°C for 3 hours, a copper-niobium heterogeneous nano-composite micro-wire with a wire diameter of 0.15 mm is obtained.
[0056] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilaments, characterized in that: The method comprises the following steps: Step 1: alternately arrange copper strips and niobium strips of the same thickness in layers and wind them into a cylinder, and then place them in an oxygen-free copper sheath to obtain a copper-niobium winding assembly composite sheath, vacuum degassing and vacuum welding the copper-niobium winding assembly composite sheath to make the interior of the oxygen-free copper sheath present a vacuum oxygen-free state, and then homogenize heating and isothermal hot extrusion deformation to form a weak connection between the internal copper layer and the niobium layer to obtain a copper-niobium composite extruded rod, and then perform multiple straight drawing, intermediate annealing and coil drawing on the copper-niobium composite extruded rod to obtain a copper-niobium composite wire with a hexagonal cross-section; Step 2: The copper-niobium composite wire with a hexagonal cross-section obtained in step 1 is used as a core wire for bundle assembly and then placed in an oxygen-free copper sheath to obtain a multi-core structure copper-niobium bundle assembly composite sheath, and the multi-core structure copper-niobium bundle assembly composite sheath is vacuum degassed and vacuum welded to make the interior of the oxygen-free copper sheath present a vacuum oxygen-free state, and then homogenized heating and isothermal hot extrusion deformation are performed to form a weak connection between the inner core wire and the outer copper layer to obtain a copper-niobium multi-core composite extruded rod, and then the copper-niobium multi-core composite extruded rod is subjected to multiple straight drawing, intermediate annealing and coil drawing to obtain a copper-niobium multi-core composite round wire; Step 3: After vacuum heat treatment, the copper-niobium multi-core composite round wire obtained in step 2 is subjected to a first multi-pass drawing and a first vacuum annealing treatment in sequence, and then a second multi-pass drawing and a second vacuum annealing treatment are sequentially performed, and then a third multi-pass drawing is sequentially performed, and after a final annealing heat treatment, a copper-niobium heterogeneous nanocomposite fine wire is obtained.
2. The method for preparing a high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilament according to claim 1, characterized in that: The thickness of the copper strip and the niobium strip in step 1 are both 0.1 mm to 0.5 mm, the diameter of the cylinder is Φ95 mm to Φ115 mm, the inner diameter of the oxygen-free copper sheath is 100 mm to 120 mm, and the wall thickness is 15 mm to 30 mm; the diameter of the copper-niobium composite extruded rod is Φ30 mm to Φ50 mm.
3. The method for preparing a high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilament according to claim 1, characterized in that: In step 1, the mass proportion of niobium element in the copper-niobium winding assembly composite sheath is 20% to 25%, the temperature of the vacuum degassing is 300° C. to 400° C., the time is 3h to 6h, and the vacuum welding adopts vacuum electron beam sealing welding with a vacuum degree of 1×10 -5 Pa~1×10 -4 Pa, the welding passes are 5 times; the temperature of the homogenizing heating is 680℃~720℃, the time is 2.5h~3.5h, the temperature of the isothermal hot extrusion deformation is 680℃~720℃, and the extrusion ratio is 7~9.
4. The method for preparing a high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilament according to claim 1, characterized in that: The deformation rate of the multi-pass straight drawing in step one is 15% to 17%, the temperature of the intermediate annealing is 670°C to 720°C, the time is 2h to 4h, the deformation rate of the disk pulling is 12% to 15%; the width across the hexagonal section is 4.5mm to 3.6mm.
5. The method for preparing a high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilament according to claim 1, characterized in that: The inner diameter of the oxygen-free copper sheath in step 2 is 100 mm to 120 mm, and the diameter of the copper-niobium multi-core composite extruded rod is Φ30 mm to Φ50 mm.
6. The method for preparing a high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilament according to claim 1, characterized in that: The temperature of the vacuum degassing in step 2 is 300°C to 400°C, and the time is 3h to 6h; the temperature of the homogenizing heating is 700°C to 720°C, and the time is 2.5h to 3.5h; the temperature of the isothermal hot extrusion deformation is 700°C to 720°C, and the extrusion ratio is 7 to 9.
7. The method for preparing high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilaments according to claim 1, characterized in that: The deformation rate of the multi-pass straight drawing in step 2 is 15% to 17%, the temperature of the intermediate annealing is 670° C. to 720° C., the time is 2h to 4h, and the deformation rate of the coil drawing is 12% to 15%; the diameter of the copper-niobium multi-core composite round wire is Φ4mm to Φ12mm.
8. The method for preparing high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilaments according to claim 1, characterized in that: The temperature of the vacuum heat treatment in step three is 650°C to 700°C, and the time is 2.5h to 3.5h; the total deformation rate of the first multi-pass drawing is 85% to 90%, the pass deformation rate is 7% to 10%, and the temperature of the first vacuum annealing treatment is 650°C to 700°C, and the time is 1h; the total deformation rate of the second multi-pass drawing is 95% to 98%, the pass deformation rate is 6% to 8%, and the temperature of the second vacuum annealing treatment is 550°C to 600°C, and the time is 1h; the total deformation rate of the third multi-pass drawing is 85% to 90%, the pass deformation rate is 12% to 24%, and the temperature of the final annealing heat treatment is 200°C to 400°C, and the time is 1h to 3h.
9. The method for preparing high temperature resistant, high strength, high electrical and thermal conductive copper-niobium heterostructured nanocomposite microfilaments according to claim 1, characterized in that: The diameter of the copper-niobium heterostructured nanocomposite microfilaments in step 3 is 0.05 mm to 0.15 mm.
Citation Information
Patent Citations
Method for preparing bronze Nb3Sn superconducting line
CN101719400A
Production method of micro-fine copper wire
CN104624707A
Superconductive multifilamentary composite - contg. superconductive alloyed vanadium or niobium wires in copper matrix
DE2557840A1
Nb3x superconductive wire material
JP1995176222A
Cited By
High-temperature superconducting MgB2 wire hot drawing preparation method based on center MgLi diffusion
CN120394592A
Ultra-long continuous nano silver wire preparation method based on Cu / PI / Ag ternary composite cluster hot drawing
CN121156075A